2016
DOI: 10.1177/0333102416679955
|View full text |Cite
|
Sign up to set email alerts
|

Does pain sensitivity change by migraine phase? A blinded longitudinal study

Abstract: Objective Studies suggest that pain thresholds may be altered before and during migraine headaches, but it is still debated if a central or peripheral dysfunction is responsible for the onset of pain in migraine. The present blinded longitudinal study explores alterations in thermal pain thresholds and suprathreshold heat pain scores before, during, and after headache. Methods We measured pain thresholds to cold and heat, and pain scores to 30 seconds of suprathreshold heat four times in 49 migraineurs and onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 85 publications
(137 reference statements)
5
49
0
Order By: Relevance
“…We only assessed mechanical sensitivity. Other studies revealed increased sensitivity for thermal pain thresholds throughout the migraine cycle [14,15]. However, the same fluctuations throughout the migraine cycle have not yet been demonstrated comprehensively for thermal pain thresholds [14] or conditioned pain modulation to assess descending pain inhibition systems.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We only assessed mechanical sensitivity. Other studies revealed increased sensitivity for thermal pain thresholds throughout the migraine cycle [14,15]. However, the same fluctuations throughout the migraine cycle have not yet been demonstrated comprehensively for thermal pain thresholds [14] or conditioned pain modulation to assess descending pain inhibition systems.…”
Section: Discussionmentioning
confidence: 97%
“…But other studies revealed that people with medication overuse, episodic and chronic migraine show failed supraspinal control of pain [10][11][12]. Failure of supraspinal control may result in loss of inhibition and hyperexcitability of trigeminovascular neurons [13] leading to dysregulation of antinociceptive processing with mechanical or thermal/or thermal hyperalgesia sensitization [14].…”
Section: Introductionmentioning
confidence: 99%
“…They found a significantly decreased habituation during the preictal phase, which normalized during the attack, and showed a trend towards elevation during the postictal phase (24). A study using laser-evoked potentials and targeting the pain pathway found, however, no difference across migraine phases (25).…”
Section: (Iii) Evoked Potentialsmentioning
confidence: 98%
“…Migraine patients undergo transient clinical and neurophysiological changes before, during and after headache attacks. These intervals define the phases of the migraine cycle, and pain perception changes transiently between the phases [1,2]. In the days and hours preceding headache, various other symptoms including yawning, nausea, changes in mood and activity, fatigue and neck symptoms emerge [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%